Adaptive Total Variation Minimization-Based Image Enhancement from Flash and No-Flash Pairs - Sang Min Yoon; Yeon Ju Lee; Gang-Joon Yoon; Jungho Yoon (The Scientific World Journal)
We present a novel approach for enhancing the quality of an image captured from a pair of flash and no-flash images. The main idea for image enhancement is to generate a new image by combining the ambient light of the no-flash image and the details of the flash image. In this approach, we propose a method based on Adaptive Total Variation Minimization (ATVM) so that it has an efficient image denoising effect by preserving strong gradients of the flash image. Some numerical results are presented to demonstrate the effectiveness of the proposed scheme.